Effectiveness of functional communication training in the regulation of self-injurious behavior in children and adolescents diagnosed with autism spectrum disorder: an empty systematic review - Tejada-Flores, Franco; Paredes-Gonzales, Yscenia (Interacciones, 2024)
Background: Self-injurious behaviors are highly prevalent in individuals with autism spectrum disorder (ASD), occurring frequently in those with associated intellectual disabilities as well as in those without intellectual impairment. Single-case studies have found that functional communication training helps regulate self-injurious behaviors and repetitive behaviors, particularly in children with ASD. However, no review identifies whether there is experimental evidence to support the use of this treatment. Objective: Our review aims to determine the efficacy of functional communication training for regulating self-injurious behavior in children and adolescents diagnosed with ASD. Methods: A systematic review was conducted.PubMed, Scopus, Web of Science, and Embase were searched for single-case experimental studies and randomized clinical trials. Results: A total of 67 studies were initially identified, of which 16 remained eligible after duplicate elimination and selection based on title and abstract. However, a thorough review of each text revealed that some needed to meet the inclusion criteria or had exclusionary elements. Therefore, they did not qualify for the next stage of the process. As a result, no publications were found that provided robust evidence to support the efficacy of functional communication training in regulating self-injurious behaviors in children and adolescents diagnosed with ASD. However, four publications met the secondary objective of identifying relationships between the proposed variables and presenting variations of the proposed intervention prototype. The quality of these publications was assessed and discussed according to the transparency recommendations of the Cochrane Effective Practice and Organization of Care guideline for reporting reviews without eligible or empty studies and the PRISMA 2020 guidelines. Conclusions: There is an urgent need for more research in this area, given the harmfulness and self-injurious behaviors, in addition to their high incidence in individuals diagnosed with ASD. This study's results help identify existing knowledge gaps and suggest new directions for research in this area.